Strategy for Strengthening Farmer Groups by Institutional Strengthening - Santoso, Purbayu Budi; Darwanto, Darwanto (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
Agriculture sector becomes a spotlight because this sector will be full of potential but the welfare of farmers who become the leading actor is not guaranteed and has a poor tendency. The purpose of this study is to formulate strategies to strengthen farmers groups in order to create the marketing of the agricultural sector that benefit farmers. The method used to achieve this goal is to use a qualitative approach and Analytical Network Process. In addition to the secondary data obtained from several agencies, this study also uses primary data obtained by in-depth interviews and observations. This research results a priority of aspects of the institutional strengthening of farmer groups as well as priority issues and priorities of the solution of each aspect. In addition, the priority of alternative strategies resulted based on the problems and solutions that have been analyzed in order to solve the problems in the institutional strengthening of farmer groups in Demak.